Development strategies for backpacker tourism development in Kota Kinabalu, Sabah, Malaysia - Johan Johnes; Jabil Mapjabil; Normah Abdul Latip; Rosazman Hussin; Mohd Umzarulazijo Umar (Malaysia Institute of Planners, 2024)
This study investigates the development strategies aimed at enhancing backpacker tourism in Kota Kinabalu, Sabah, with a focus on social, environmental, and economic dimensions. This study uses quantitative methods through the distribution of questionnaires to study the behaviour and opinions of backpackers in Kota Kinabalu. This study focuses on respondents at backpacker accommodation and tourist destinations in Kota Kinabalu. A total of 228 backpackers participated in this study. These strategies encompass social development, environmental development, and economic development, and encompass initiatives such as community engagement, environmental conservation, and collaboration with local businesses. Achieving a balance between economic growth and social and environmental sustainability is crucial in maximizing the potential of backpacker tourism. Successful implementation of these strategies necessitates the active involvement of various stakeholders, including government agencies, local communities, and the tourism industry. Integrating these strategies into destination management plans will elevate the backpacker tourism experience and facilitate sustainable growth. Further research and collaboration among stakeholders are imperative to effectively implement these strategies and harness the opportunities presented by backpacker tourism in the region.